A study on mathematics learning strategies among pre-university students - Zainuddin, Nur Mazliyana; Kaharudin, Norashikin; A. Hamid, Nor Hafizah (Universiti Islam Selangor, 2024)
Mathematics is a fundamental subject for everyday problem-solving until advanced scientific research. However, for many students, Mathematics can be a challenging subject. To effectively learn and master mathematical concepts, it is essential to apply effective learning strategies. Therefore, this research aims to analyze students’ learning strategies in Mathematics. The study employed a quantitative research design with a structured questionnaire as the primary data collection instrument. The questionnaire is divided into two main parts: Part A (Demographic Profile) and Part B (Learning Strategies). Part B has three components: cognitive, metacognitive self-regulation, and resource management. A 5-point Likert scale: never, rarely, sometimes, very often, and always was used to investigate students’ frequency in using specific learning strategies. About 198 respondents from the Science and Engineering Programme in the Centre of Foundation Studies, UiTM responded to the survey. The study used descriptive analysis to analyze the data gathered. The results show that the students utilized cognitive strategy in learning Mathematics, whereby students rehearse, organize, elaborate, and apply critical thinking. The respondents were aware of metacognitive strategies and could manage available resources in learning Mathematics. The study benefits students, educators and the Ministry of Higher Education to improve the quality of learning and education in Mathematics, especially at the higher education level.